Analysis of 16 phthalate esters in wastewater from textile plants using headspace solid-phase microextraction and gas chromatography with mass spectrometric detection. Issue 3 (February 2021) - Li, Ying; Ye, XiWen; Niu, ZengYuan; He, Jing; Luo, Xin; Ma, Qiang
Solid-phase microextraction (SPME) with a 100-µm polydimethylsiloxane (PDMS) fiber coupled to gas chromatography–mass spectrometry was used to determine 16 phthalate esters (PAEs) in wastewater from textile processing plants. Some of the 16 PAEs that exist as mixtures of isomers were identified and quantified. We investigated the matrix effect and evaluated a qualification and quantitation method for determining trace amounts of PAEs in wastewater from textile processing plants. The major advantages of this approach are the reduced matrix effects from the textile wastewater and the compatibility with the standard addition method (SAM) for PAE quantitation. Moreover, the developed method has low reagent and solvent consumption, does not require clean-up or evaporation steps and involves minimal sample manipulation. Two fiber coatings, 85-µm polyacrylate and 100-µm PDMS, were tested. The variables affecting SPME absorption, such as the sample temperature, extraction time and salt concentration, were studied. The final conditions were an extraction temperature of 95℃, an extraction time of 30 min and a salt concentration of 0.3 g/mL. The SAM was used to analyze and quantify samples. The linear range was between 5 and 20 µg/L, and the limits of detection of the method were between 0.5 and 5 µg/L. Finally, the precision of the phthalate quantitation was also evaluated.